2021
DOI: 10.3390/ijms22052535
|View full text |Cite
|
Sign up to set email alerts
|

VTRNA2-1: Genetic Variation, Heritable Methylation and Disease Association

Abstract: VTRNA2-1 is a metastable epiallele with accumulating evidence that methylation at this region is heritable, modifiable and associated with disease including risk and progression of cancer. This study investigated the influence of genetic variation and other factors such as age and adult lifestyle on blood DNA methylation in this region. We first sequenced the VTRNA2-1 gene region in multiple-case breast cancer families in which VTRNA2-1 methylation was identified as heritable and associated with breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 70 publications
4
23
1
Order By: Relevance
“…Genotypes were obtained using the Infinium OncoArray-500K BeadChip (Illumina, San Diego, CA, USA) [ 29 , 35 ] and imputed using the Michigan imputation server [ 36 ] and IMPUTE version 2 [ 37 ] with the 1000 Genomes Project dataset (phase 3) as the reference panel. To avoid bias due to confounding by shared environment among close relatives, the 4306 participants were confirmed to be unrelated, i.e., any pair among them was with a genetic relationship >0.05 (4th degree or closer relationship) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypes were obtained using the Infinium OncoArray-500K BeadChip (Illumina, San Diego, CA, USA) [ 29 , 35 ] and imputed using the Michigan imputation server [ 36 ] and IMPUTE version 2 [ 37 ] with the 1000 Genomes Project dataset (phase 3) as the reference panel. To avoid bias due to confounding by shared environment among close relatives, the 4306 participants were confirmed to be unrelated, i.e., any pair among them was with a genetic relationship >0.05 (4th degree or closer relationship) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…To assess the potential influence of underlying genetic variants on our findings, we first corrected DNA methylation values using linear mixed models with M-values as the outcome, age, sex, sample type, white blood cell proportions (estimated using the Houseman algorithm [ 39 ]), and 20 genetic principal components to account for population structure as fixed effects, and study, plate, and slide of the assay as random effects, similar to a previous publication [ 38 ]. We then used linear regression to assess associations between the corrected M-values at the 45 CpGs and genetic values at the four variants.…”
Section: Methodsmentioning
confidence: 99%
“…The methylation status of this epiallele has also been associated with allergies [25], asthma [26], infections [27], and inflammation [28]. Previous studies have not found indications that genetics impact the methylation status of the nc886 epiallele [4,18,21,29], but a study has suggested that one SNP (rs2346018) is associated with the DNA methylation levels in the centromeric CTFC binding site flanking the nc866 epiallele [1].…”
mentioning
confidence: 99%
“…Among the 4,511 participants, DNA of 4,307 were extracted at baseline recruitment (1990-1994). QC details for measures of genome-wide DNA methylation have been reported previously [34-36, 44]. Briefly, we removed probes with missing rate > 20% and probes on Y-chromosome, and ultimately retained 484,431 CpG sites with their beta values for each sample.…”
Section: Methodsmentioning
confidence: 99%